Pengaruh Inovasi Produk dan Kualitas Pelayanan terhadap Keputusan Pembelian pada Buket Belikadoyuk Karawang - Karin, Karina Ristiyana; Puji Isyanto; Neni Sumarni (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to determine the influence of product innovation and service quality on purchasing decisions at Buket Belikadoyuk Karawang. The method used in this research is a quantitative method. The research was conducted on Bouquet Belikadoyuk Karawang, with a sample size of 96 respondents with a population of Buket Belikadoyuk consumers who specifically live in Karawang Regency. Sampling in this research used a purposive sumpling technique. The research results show that the product innovation variable and the service quality variable at Buket Belikadoyuk Karawang have a positive effect on the purchasing decision variable. So, the more frequently you innovate appropriate products, the more purchasing decisions will be followed. Service quality also has a direct impact on purchasing decisions. This indicates that maintaining good service quality at Buket Belikadoyuk Karawang is very important to improve consumer purchasing decisions. Thus, the better the product innovation and service quality provided by Buket Belikadoyuk Karawang, the consumer purchasing decisions will increase. These findings underline the importance of carrying out product innovation and providing quality services as strategic steps for consumer purchasing decisions.